From Tradition to Mainstream: Understanding the Integration of Islamic Law in Various Global Settings - Suud Sarim Karimullah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
The study highlights the importance of integrating Islamic law in global legal settings, enriching the legal framework, and promoting interreligious dialogue. This is an important area that needs to be understood and taken seriously in the context of ongoing world changes. The study used a qualitative approach to analyze academic literature, legal documents, and related research reports from various sources. The research findings identify several significant examples of integration of Islamic law in different global settings, including Muslim and non-Muslim majority countries. The integration of Islamic law in a worldwide legal environment offers meaningful potential. First, values such as social justice, balance, and common good in Islamic law can provide a different and complementary perspective to the principles of secular law. This impacts more inclusive and fair policies for the Muslim community. Second, the integration of Islamic law can better facilitate interreligious dialogue. Non-Muslim communities' more profound understanding of Islamic law may open the way for constructive dialogue, mutual understanding, and cooperation in addressing global legal issues. This has the potential to reduce tensions and increase interreligious tolerance. However, challenges and controversies are also part of integrating Islamic law. Recognition of the validity and relevance of Islamic law in more comprehensive legal settings is still doubted by some. At the same time, differences in interpretation and implementation can lead to tensions in diverse societies.